CMET-46. INITIAL CLINICAL AND ADVANCED IMAGING OUTCOMES FROM A MULTI-INSTITUTIONAL PHASE I DOSE-ESCALATION TRIAL OF RRX-001 PLUS WHOLE BRAIN RADIATION FOR PATIENTS WITH BRAIN METASTASES. (5th November 2018) - Kim, Michelle; Parmar, Hemant; Aryal, Madhava; Schipper, Matthew; Devasia, Theresa; Kesari, Santosh; Morikawa, Aki; Spratt, Daniel; Junck, Larry; Hayman, James; Lawrence, Theodore; Tsien, Christina; et al.
Abstract: BACKGROUND: RRx-001, a novel redox modulator was evaluated as a potential radiosensitizer with WBRT in a multicenter phase I trial for adults with brain metastases. The primary endpoint was to determine MTD. Secondary endpoints included intracranial response rate (IRR), survival and correlation of DCE-MRI parameters with outcome. METHODS: Dose-escalation was managed by a TITE-CRM design to establish MTD at a 20% estimated DLT rate with four planned dose levels (5, 8.4, 16.5, 27.5 mg/m2). RRx-001 was given pre-WBRT (30 Gy/10 fractions) then twice weekly during WBRT. Target accrual was 30 patients. Correlative DCE-MRI was performed in a subset of patients at baseline, 24 hours post-RRx pre-WBRT, 1 and 4 months. Linear mixed models were used to correlate baseline and change in 24-hour Vp (plasma volume) with change in tumor volume. RESULTS: Between 2/2015-2/2017, 31 patients were enrolled across 5 centers. Two patients dropped out at baseline, and seven were treated with RRx/concurrent temozolomide to be reported separately, for a total of 22 evaluable patients. Median age was 60 years (range 35–85), 13 were male, 55% had melanoma and 23% had NSCLC. No DLTs were observed within 28 days of treatment and 5 patients were treated at the highest dose level. IRR was 50%, five patients survived > 12 months, 3 were alive at last follow-up. Among 10 evaluable patients undergoing DCE-MRI with 64 total lesions at baseline, lower baseline Vp (p=0.002) and reduction in Vp at 24 hours (p=0.001) were associated with reduced tumor volume at 1 and 4 months. CONCLUSION: RRx-001+WBRT appears well-tolerated in adults with brain metastases, with several long-term survivors and IRR of 50%. Following a single dose of RRx, a reduction in Vp is associated with tumor response at 1 and 4 months, suggesting activity within tumor vasculature and utility as a biomarker of longer-term response.